2021
DOI: 10.1159/000517584
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D and Risk of Stroke: A PRISMA-Compliant Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> Previous studies have shown inconsistent results for associations between vitamin D and risk of stroke. We gathered the existing published articles and conducted this meta-analysis with the aim to explore the association between vitamin D and risk of stroke. <b><i>Methods:</i></b> We searched for articles exploring the association between vitamin D and risk of stroke and published before April 2021 in the following databases: PubMed, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…This is also confirmed by a meta-analysis by Zhou, Wang, Huang et al, which also found that low vitamin D levels were not associated with hemorrhagic stroke [72]. There is no lack of systematic reviews and meta-analyses that deny the protective effect of vitamin D [73] and confirm that low vitamin D levels are associated with an increased risk of stroke, but additional supplements have no impact on risk reduction [74].…”
Section: Vitamin D and Stroke Incidencementioning
confidence: 64%
“…This is also confirmed by a meta-analysis by Zhou, Wang, Huang et al, which also found that low vitamin D levels were not associated with hemorrhagic stroke [72]. There is no lack of systematic reviews and meta-analyses that deny the protective effect of vitamin D [73] and confirm that low vitamin D levels are associated with an increased risk of stroke, but additional supplements have no impact on risk reduction [74].…”
Section: Vitamin D and Stroke Incidencementioning
confidence: 64%
“…According to recent meta-analyses involving 15 RCTs and more than 80,000 participants ( 15 ), there was no significant benefit from vitamin D supplementation for stroke prevention (Su et al: HR = 1.05, 95% CI: 0.96–1.14, P = 0.425). In total three other meta-analyses ( 26 , 28 , 53 ) also failed to demonstrate a reduction in stroke incidence with vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D also exhibits several neuroprotective effects ( 6 8 ), namely, enhancing synaptic plasticity ( 9 ), reducing oxidative stress ( 10 ), and reducing brain damage and inflammatory responses in ischemic and neurodegenerative diseases ( 11 , 12 ). Several studies have demonstrated that vitamin D deficiency was an independent risk factor for ischemic stroke ( 13 15 ). Vitamin D deficiency has been associated with increased severity and poor prognosis following stroke ( 7 , 8 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher inflammatory status underpinning the vitamin D deficiency might also explain its role in neurological diseases, such as multiple sclerosis [ 14 ], stroke [ 28 ], and Parkinson disease [ 15 ]. These findings can support a possible role of vitamin D deficiency on brain health, notably for the risk of dementia and cognitive impairment; indeed, Navale et al showed that hypovitaminosis D was associated with neuroimaging outcomes and a higher risk of dementia and stroke [ 29 ].…”
mentioning
confidence: 99%